Excretion of enterovirus 71 in persons infected with hand, foot and mouth disease - Li, Jie (BioMed Central, 2013)
BACKGROUND: Hand, foot and mouth disease (HFMD) is a common illness in young children. It also can be seen in adults occasionally. Enterovirus 71 (EV71), a pathogen that causes not only HFMD but also neurological complications and even death, has caused many HFMD outbreaks in China. However, till now the data about the duration of EV71 shedding is very limited. RESULTS: A total of 136 throat swabs and fecal samples were collected from 27 children and 3 adults, which includs 7 close contacts, 9 mild cases and 14 severe cases,. The participants were divided into three groups namely, severe case group, mild case group and close contact group. All the samples were assayed with real-time polymerase chain reaction (PCR). Kruskal-Wallis Test was employed to compare the difference in duration of viral RNA shedding among three groups. The results showed that significant difference in duration of EV71 shedding was found among three groups (P < 0.01). The longest duration of EV71 shedding in fecal samples is 54 days and 30 days in throat swabs. CONCLUSIONS: HFMD is characterized by extended excretion of EV71. Our results suggest that the duration of EV71 shedding is correlated with the severity of the disease. EV71 shedding through feces can persist more than 54 days. Prolonged virus shedding is a potential risk factor of proliferating HFMD epidemic.